2018
DOI: 10.3390/educsci8020070
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting MOOC Usage by Students in Selected Ghanaian Universities

Abstract: There has been widespread criticism about the rates of participation of students enrolled on MOOCs (Massive Open Online Courses), more importantly, the percentage of students who actively consume course materials from beginning to the end. The current study sought to investigate this trend by examining the factors that influence MOOC adoption and use by students in selected Ghanaian universities. The Unified Theory of Acceptance and Use of Technology (UTAUT) was extended to develop a research model. A survey w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
91
4
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(108 citation statements)
references
References 42 publications
11
91
4
2
Order By: Relevance
“…Nordin et al (2015) found positive results of all the UTAUT factors toward MOOCs. Fianu et al (2018) found that performance expectancy positively influenced MOOC usage intentions in Ghana. Such inconsistency of findings leads to further investigation.…”
Section: The Utaut Modelmentioning
confidence: 96%
“…Nordin et al (2015) found positive results of all the UTAUT factors toward MOOCs. Fianu et al (2018) found that performance expectancy positively influenced MOOC usage intentions in Ghana. Such inconsistency of findings leads to further investigation.…”
Section: The Utaut Modelmentioning
confidence: 96%
“…For example, in a survey of learning professionals, "most of the But most of all, motivation stems from autonomy, that is, the ability to manage one's own course of studies. "It's not social influence", write Fianu et al (2018). It is traceable to the pedagogy and the learning environment.…”
Section: Motivationmentioning
confidence: 99%
“…From the concept of FC, the convenience conditions affecting the use of the mobile Internet are discussed. Vongjaturapat [62] and Fianu [63] disclosed that FC notably influences usage intention. Therefore, the following hypothesis was formed:…”
Section: Hypothesis 4b (H4b) User Satisfaction Positively Affects Usmentioning
confidence: 99%